Enhancing the sulfidation of smithsonite by superficial dissolution with a novel complexing agent. (December 2017) - Wu, Dandan; Ma, Wenhui; Wen, Shuming; Deng, Jiushuai; Bai, Shaojun
Highlights: Sodium sulfosalicylate has been used to enhance sulfidation and flotation of smithsonite. The surface solubility of enhanced sulfurized smithsonite was significantly decreases. Smithsonite was more easily sulfurized by sodium sulfide with sodium sulfosalicylate. Abstract: Sodium sulfosalicylate was used for the first time to enhance the sulfidation–flotation of smithsonite. Sodium sulfosalicylate could facilitate the flotation of smithsonite, and increase the flotation recovery by ∼28%. Inductively coupled plasma analysis indicated that the surface dissolution of the enhanced sulfurized smithsonite decreased significantly. X-ray photoelectron spectral analysis revealed that smithsonite can be sulfurized easily by using sodium sulfide with sodium sulfosalicylate. The effect of sodium sulfosalicylate on zinc-oxide ore flotation has been verified. Compared with the direct sulfidation–flotation of zinc-oxide ore, enhanced sulfidation–flotation can improve the concentrate grade by 3.83% and the concentrate recovery by 7.63%. Therefore, the addition of sodium sulfosalicylate played a significant role in smithsonite sulfidation, which improves the flotation performance.